FESTUNG: A MATLAB / GNU octave toolbox for the discontinuous Galerkin method ; part IV: generic problem framework and model-coupling interface - Reuter, Balthasar; Rupp, Andreas; Aizinger, Vadym; Frank, Florian; Knabner, Peter (Communications in computational physics, 2020)
This is the fourth installment in our series on implementing the discontinuous Galerkin (DG) method as an open source MATLAB / GNU Octave toolbox. Similarly to its predecessors, this part presents new features for application developers employing DG methods and follows our strategy of relying on fully vectorized constructs and supplying a comprehensive documentation. The speciﬁc focus of the current work is the newly added generic problem implementation framework and the highly customizable model-coupling interface for multi-domain and multi-physics simulation tools based on this framework. The functionality of the coupling interface in the FESTUNG toolbox is illustrated using a two-way coupled free-surface / groundwater ﬂow system as an example application.
Gesehen am 10.08.2020